The SCREENING SKIN INFECTIONS IN STUDENTS OF TANJUNG PASIR AL-AWWABIEN ISLAMIC BOARDING SCHOOL, JAMBI - Husman, Lipinwati; Hasna Dewi; Hanina; Fairuz; Putri Sari Wulandari; Ivo Amrina Rasyada; Jhanakalyani II (Universitas Jambi, 2025)
Islamic boarding schools are faced health problems with various types of diseases such as skin diseases and TB. Skin infection can be caused by bacteria, fungi, parasites, which have the potential to be contagious if students does not practice Clean and Healthy Living Behavior (PHBS). Direct microscopic examination is the easiest, most affordable, and specific method for diagnosis. Therefore, the Community Service Team from the Faculty of Medicine and Health Sciences, University of Jambi (FKIK UNJA), provided education on PHBS, conducted skin scraping examinations, and it’s treatments. The objective of this community service is to describe the skin infection with direct microscopic examination skin scraping using KOH among students at the Tanjung Pasir Al-Awwabien Islamic Boarding School, Jambi. The implementation of community service activities on Sunday, 11 August 2024 at the Tanjung Pasir Al-Awwabien Jambi Islamic Boarding School. The direct skin scraping examinations were carried out by scraping the affected skin area with a scalpel onto a glass slide, followed by the application of one drop of 10% KOH solution. The results were then analyzed using a microscope, and treatments were provided accordingly. The screening session was attended by 59 students with systemic symptoms, while 13 participants underwent direct skin scraping examinations. Among the students with skin disease, the majority were 14-yo. Most of the direct examinations did not detect spores, hyphae, or mites, and the most common diagnosis was tinea among the types of skin disease. The direct skin scraping examinations supports the diagnosis of skin infection, and it’s treatment, which is expected to help prevent the spread of skin diseases. Keywords: Skin Infection, Islamic boarding school, PHBS, Skin scraping